Autonomy of work and job satisfaction in workers of a Peruvian university - Faya Salas, Adela (2018)
The objective of the research was to determine the relationship between the autonomy of work and the job satisfaction of the administrative workers of a Peruvian university. The hypothetical deductive method was used, based on a non-experimental, cross-section quantitative design approach. A questionnaire was applied to 122 workers. The results allowed the researchers to determine the direct, moderate and significant correlation, with a Spearman correlation coefficient Rho = 0.651 ** and 0.626 ** and a (Bilateral) significance = 0.000 (p <.05). Therefore, it was concluded that when work autonomy is pr, the level of job satisfaction is high in workers of both sexes.